Artifacts, Identity and Youth: A Cultural Intervention with Pacific Islander Young People Who Offend in Western Sydney, Australia. (July 2015) - Blake, Meredith; Liddell, Marg; Singh, Supriya
Abstract This article provides information on the evaluation of a project between the Australian Museum and the Juvenile Justice department in New South Wales, Australia, where young people who offend of Pacific Islander heritage were introduced to an extensive range of Pacific Islander cultural materials. The key assumption of the project was that young Pacific Islander people who offend struggled with cultural identity issues, and that a meaningful connection with their heritage would improve cultural knowledge and pride—thereby reducing their involvement in crime. However, this assumption was not borne out by the study's results. Firstly, the twenty‐two Pacific Islander young offender study participants were already proud of their heritage, and comfortable in their cultural identities. Secondly, though they enjoyed their visit to the museum, most did not want to visit again, so there was no sustained engagement. Thirdly, the Museum program was not designed as part of a holistic approach with multiple strategies which addressed the complex reasons for youth offending. Despite eight out of the twenty‐two participants reoffending after the Museum visit, there was enough potential for the rehabilitative intervention that the Museum was granted funding to take its program to the community and make it more user‐centered. This, it is hoped, will set it on a path towards more sustained engagement, and the potential for a greater influence on Pacific Islander youth.